Intermittent Hypoxic Training as an Effective Tool for Increasing the Adaptive Potential, Endurance and Working Capacity of the Brain - Rybnikova, Elena A.; Nalivaeva, Natalia N.; Zenko, Mikhail Y.; Baranova, Ksenia A. (Frontiers in Neuroscience, 2022)
This review is devoted to the phenomenon of intermittent hypoxic training and is aimed at drawing the attention of researchers to the necessity of studying the mechanisms mediating the positive, particularly neuroprotective, effects of hypoxic training at the molecular level. The review briefly describes the historical aspects of studying the beneficial effects of mild hypoxia, as well as the use of hypoxic training in medicine and sports. The physiological mechanisms of hypoxic adaptation, models of hypoxic training and their effectiveness are summarized, giving examples of their beneficial effects in various organs including the brain. The review emphasizes a high, far from being realized at present, potential of hypoxic training in preventive and clinical medicine especially in the area of neurodegeneration and age-related cognitive decline.